Study and Application of Mathematical Analysis Model for Pollution Diffusion in Plain Rivers - SUN Rufei; YAO Cheng; HU Kehong; YU Chao (Renmin Zhujiang)
With the increasing level of urbanization, the water environment of river networks is becoming overwhelmed. In the emergency scenario, the effective simulation and characteristic statistics of the pollution going into the river have become one of the key directions of the current water environment control and prevention research. By sorting out the business demands of water environment prevention and control in the plain area, the technical system of river pollution diffusion analysis and mathematical analysis model of river pollution diffusion (MAM-RPD) are built. These solutions realize the simulation calculation and characteristic distribution statistics of river pollutant diffusion, providing reasonable and effective data support for river water pollution emergencies. The MAM-RPD model is applied in a river in the southern region to simulate and analyze the temporal and spatial characteristics of pollutant diffusion. The application generates the output results with a good supporting effect, which helps improve the efficiency of management departments in dealing with water pollution emergencies. The results showed that the river reach is in the alarm state for more than 4 hours, which requires prompt external intervention. The mean pollutant concentration of the river reach increases and then decreases, reaching the maximum value of 1.569 4 mg/L at the 30th minute, and then gradually decreases. The overall pollution of the characteristic sections near the emission point source is more serious than that of other sections.